Micro-simulation of the impact of different speeds on safety road travel and urban travel time: case study in the city of Guimarães - Ribeiro, Paulo (2019)
In recent days, the use of micro-simulation as an additional tool for the study of the network makes this management faster and more efficient, avoiding in situ studies. However, although it is a useful tool, it is necessary that the model under study is the best represented possible in order to obtain results that best fit the reality of the road, and a poor calibration of the model can provide results that do not fit the good management of the road under study. In this sense, using micro-simulation, more precisely to the VISSIM PTV software, a road network at the microscopic level will be evaluated as well as the parameters that most influence the route of the users within that network. The parameters will be modified according to the modeler so as to obtain a model as close to reality as possible. The most appropriate criteria for the calibration and validation of the model will also be chosen. The road safety of the network will also be analyzed using the SSAM software. Here the network's points of conflict will be analyzed, characterizing them as to the type and its severity. Subsequently, a sensitivity analysis will be introduced, where some parameters will be modified individually or together, in order to assess their influence on the network, thus assessing the importance of each in the vehicles.